Religiosidade ou espiritualidade são fatores que influenciam a adesão ao flexitarianismo? - Ramos, Vanessa Almeida Nogueira (2022)
Flexitarianism is a dietary pattern that seeks to reduce the consumption of animal meat without its total exclusion. As far as we know, no scientific studies have sought to analyze whether religious or spiritual motivations are related to flexitarianism. As flexitarianism is considered a flexible aspect of secular vegetarianism in the 21st century, we believe that religious motivations are not relevant to explain the adherence of its adherents. Thus, the objective of this work is to evaluate whether religion and spirituality are motivating factors for adherence to flexitarianism. We used primary data from a cross-sectional survey, which collected information from 1029 Brazilian adults who declared themselves as flexitarians through an online form. The results of our study show that the majority of the population that declares itself to be flexitarian has no religion and the motivation “religion, beliefs or spirituality” only explains the behavior of about 4% of the adherents. Despite a small group referring to a religious or spiritual motivation in the adherence behavior, a large part of the flexitarian population refers to it as spiritualized (86%). Thus, we conclude that flexitarianism today does not have a link with the traditional religious question, but that it can connect to a broader idea of spirituality.